2017
DOI: 10.6002/ect.2016.0210
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Biliary complications are common after living-donor liver transplant. This retrospective study reviewed our experience with biliary complications in recipients of living-donor liver transplant. Materials and Methods: Over our 9-year study period, 120 patients underwent living-donor liver transplant. Patients were divided into 2 groups, with group A having biliary complications and group B without biliary complications. Both groups were compared, and different treatment modalities for biliary compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(64 reference statements)
2
1
0
Order By: Relevance
“…During the study period, 83 (out of 376 patients who underwent LDLT) patients developed biliary stricture, representing 22% of all recipients. This finding agrees with Sarhan et al ( 7 ) who reported an overall stricture rate of 21.7% in patients with LDLT. It is also consistent with Kim ( 17 ) in which biliary stricture occurred in 19.5% of recipients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During the study period, 83 (out of 376 patients who underwent LDLT) patients developed biliary stricture, representing 22% of all recipients. This finding agrees with Sarhan et al ( 7 ) who reported an overall stricture rate of 21.7% in patients with LDLT. It is also consistent with Kim ( 17 ) in which biliary stricture occurred in 19.5% of recipients.…”
Section: Discussionsupporting
confidence: 93%
“…During the study period, 83 (out of 376 patients who underwent LDLT) patients developed biliary stricture, representing 22% of all recipients. This finding agrees with Sarhan et al (7) who reported an overall stricture rate of 21.7% Relatively, early detection of biliary stones may be related to multiple risk factors in the same patient and the successful follow-up program that allowed us to detect the problem early.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation